Understanding Global Defense Budgeting Dynamics: A Systematic Literature Review on Economic and Geopolitical Factors - Muchamad Bachtiar; Irdam Ahmad; Zainal Abidin Sahabuddin; Trismadi (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Defense budgeting plays a critical role in shaping a nation's strategic and military capabilities, reflecting its global positioning and priorities. It is influenced by a complex intersection of global politics, security concerns, and economic factors. Understanding these dynamics is crucial for guiding national policies and strategies.Purpose: This study aims to analyze the intricate factors shaping military expenditures globally, with a focus on understanding the role of Gross Domestic Product (GDP) growth, geopolitical tensions, and international political dynamics.Design/methodology/approach: The research employs a systematic literature review (SLR) guided by the PRISMA protocol to synthesize insights from existing studies. Utilizes Scopus-indexed journals to ensure the quality and reliability of the literature.Findings/Results: The findings highlight GDP growth as a central determinant of military expenditure, influenced by geopolitical interdependencies and regional dynamics. Theoretical frameworks, such as